The Slave Market in Rio de Janeiro circa 1869: Context, Movement and Social Experience - Frank, Zephyr; Berry, Whitney (Journal of Latin American geography, 2010)
The slave market in Rio de Janeiro was transformed over the course of the nineteenth century. Prior to 1850, slaves poured into the city from Africa via the Atlantic trade. Buying and selling slaves then shifted to a local market typified by individual sales. Rather than a concentrated process dominated by formal market spaces and professional slave traders, the slave market in Rio de Janeiro was, by 1869, a continuous process that encompassed every neighborhood in the city. Mapping the origins, destinations, and characteristics of slaves, using detailed transaction data from 1869, highlights the ubiquity of slavery in Rio de Janeiro and the movement of slaves into new environments. O mercado de escravos no Rio de Janeiro foi transformado ao longo do século XIX. Antes de 1850, escravos africanos chegaram na cidade através do comércio atlântico. A compra e venda de escravos, então, foi transferido a um mercado local caracterizado por vendas individuais. Em vez de um processo concentrado e dominado por espaços formais e negociantes de escravos, o mercado de escravos no Rio de Janeiro foi, em 1869, um processo contínuo que abrangeu todos os bairros da cidade. Mapeando as origens, destinos e características de escravos, utilizando dados detalhados sobre as transaçoes, a partir de 1869, destaca a presença onipresente da escravidão no Rio de Janeiro e o movimento de escravos à ambientes novos.